2023
DOI: 10.20517/evcna.2023.11
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in the treatment and prevention of osteoarthritis: can horses help us translate this therapy to humans?

Abstract: Osteoarthritis (OA) is a common joint disease affecting humans and horses, resulting in significant morbidity, financial expense, and loss of athletic use. While the pathogenesis is incompletely understood, inflammation is considered crucial in the development and progression of the disease. Mesenchymal stromal cells (MSCs) have received increasing scientific attention for their anti-inflammatory, immunomodulatory, and pro-regenerative effects. However, there are concerns about their ability to become a commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…5 Constituting a rapidly expanding field of research, extracellular vesicles (EVs) have been identified to play a major role in both joint homeostasis and the pathophysiology of PTOA in humans and horses. 6,7 EVs are small, membrane-enclosed vesicles that are secreted by most mammalian cells. There are 3 subtypes of EVs that are classified based on their biogenesis and size as exosomes (approx 30 to 100 nm), microvesicles (approx 100 to 1,000 nm), and apoptotic vesicles (approx 1,000 to 5,000 nm).…”
mentioning
confidence: 99%
“…5 Constituting a rapidly expanding field of research, extracellular vesicles (EVs) have been identified to play a major role in both joint homeostasis and the pathophysiology of PTOA in humans and horses. 6,7 EVs are small, membrane-enclosed vesicles that are secreted by most mammalian cells. There are 3 subtypes of EVs that are classified based on their biogenesis and size as exosomes (approx 30 to 100 nm), microvesicles (approx 100 to 1,000 nm), and apoptotic vesicles (approx 1,000 to 5,000 nm).…”
mentioning
confidence: 99%